2017
DOI: 10.1136/bmj.j3984
|View full text |Cite
|
Sign up to set email alerts
|

Trends for prevalence and incidence of resistant hypertension: population based cohort study in the UK 1995-2015

Abstract: Objective To estimate the incidence and prevalence of resistant hypertension among a UK population treated for hypertension from 1995 to 2015. Design Cohort study. Setting Electronic health records from the UK Clinical Practice Research Datalink in primary care. Participants 1 317 290 users of antihypertensive drugs with a diagnosis of hypertension. Main outcome measures Resistant hypertension was defined as concurrent use of three antihypertensive drugs inclusive of a diuretic, uncontrolled hypertension (≥140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 38 publications
4
43
0
3
Order By: Relevance
“…Prevalensi penyakit ini semakin meningkat di seluruh dunia, diperkirakan satu dari empat orang penduduk di negara maju menderita hipertensi. 1,2 Jika penyakit ini tidak terkontrol maka akan menyerang organ yang dapat menyebabkan suatu serangan jantung, stroke, gangguan ginjal, serta berbagai komplikasi penyakit lainnya. Beberapa penelitian lain melaporkan bahwa hipertensi yang tidak di kontrol dengan baik memberikan peluang tujuh kali lebih besar menyebabkan stroke, enam kali lebih besar congestive heart failure, dan tiga kali lebih besar serangan jantung.…”
Section: Pendahuluanunclassified
“…Prevalensi penyakit ini semakin meningkat di seluruh dunia, diperkirakan satu dari empat orang penduduk di negara maju menderita hipertensi. 1,2 Jika penyakit ini tidak terkontrol maka akan menyerang organ yang dapat menyebabkan suatu serangan jantung, stroke, gangguan ginjal, serta berbagai komplikasi penyakit lainnya. Beberapa penelitian lain melaporkan bahwa hipertensi yang tidak di kontrol dengan baik memberikan peluang tujuh kali lebih besar menyebabkan stroke, enam kali lebih besar congestive heart failure, dan tiga kali lebih besar serangan jantung.…”
Section: Pendahuluanunclassified
“…After excluding patients with insufficient data or follow‐up (9%) and poor adherence, they found that 1.9% of patients developed TRH over a median 1.5 years and observed a crude incidence rate of 0.7 per 100 patient‐years. In the second study, researchers analyzed EHR data from 1.32 million primary care patients with treated hypertension contained in the UK Clinical Practice Research Datalink database for cases of TRH (again, using the prior US definition and excluding patients for nonadherence) . From 1995 to 2015, they found a crude incidence rate ranging between 0.4 and 2.1 per 100 person‐years, and point prevalences between 1.8% and 8.2%, depending on the year.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two prior studies have published data on TRH incidence, both of which used electronic health record (EHR) data from real-world treatment settings, and both assessed incidence of TRH using the former definition (with BP control as <140/90 mm Hg) under a BP target < 140/90 mm Hg. 16,17 In the first study, researchers assessed the incidence of TRH among 205 750 patients with incident treated hypertension in the Kaiser Permanente system. 16 After excluding patients with insufficient data or follow-up (9%) and poor adherence, they found that 1.9% of patients developed TRH over a median 1.5 years and observed a crude incidence rate of 0.7 per 100 patient-years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistant hypertension (RH) is defined as BP that remains ≥140/90mmHg despite being treated with maximum, or best tolerated doses, of three or more anti‐hypertensive drugs, one of which should be a diuretic . Almost 7% of the treated hypertensive population in the United Kingdom has RH, representing approximately 800 000 people . Those with RH have worse health outcomes than those with “standard” hypertension, which double the risk of cardiovascular events .…”
Section: Introductionmentioning
confidence: 99%